2023
DOI: 10.3390/foods12152859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperatures on Drying Kinetics, Extraction Yield, Phenolics, Flavonoids, and Antioxidant Activity of Phaleria macrocarpa (Scheff.) Boerl. (Mahkota Dewa) Fruits

Fatin Nurain Stephenus,
Mohammad Amil Zulhilmi Benjamin,
Adilah Anuar
et al.

Abstract: Phaleria macrocarpa or ‘Mahkota Dewa’ is a popular plant found in Malaysia as it is a valuable source of phytochemicals and therapeutic properties. Drying is an essential step in the storage of P. macrocarpa fruits at an industrial level to ensure their availability for a prolonged shelf life as well as preserving their bioactive compounds. Hence, this study evaluates the effect of different temperatures on the drying kinetics, extraction yield, phenolics, flavonoids, and antioxidant activity of P. macrocarpa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…value of HAD at 60 °C was consistent with previous publications [39,40], ranging from 3.210 × 10 −9 to 2.840 × 10 −8 m 2 /s for the drying of tomato and P. macrocarpa fruits with similar geometries. Furthermore, the Deff value of the RFHAD method were 1.67 times higher compared to that of HAD, which demonstrated that the moisture transfer efficiency of the RFHAD process was much higher than that of HAD.…”
Section: Effective Moisture Diffusivitysupporting
confidence: 91%
See 1 more Smart Citation
“…value of HAD at 60 °C was consistent with previous publications [39,40], ranging from 3.210 × 10 −9 to 2.840 × 10 −8 m 2 /s for the drying of tomato and P. macrocarpa fruits with similar geometries. Furthermore, the Deff value of the RFHAD method were 1.67 times higher compared to that of HAD, which demonstrated that the moisture transfer efficiency of the RFHAD process was much higher than that of HAD.…”
Section: Effective Moisture Diffusivitysupporting
confidence: 91%
“…As expected, the higher D eff values were obtained for RFHAD (6.889 × 10 −9 m 2 /s) and RFHAD + EAR (6.062 × 10 −9 m 2 /s), whereas the lower D eff values were obtained for HAD (4.124 × 10 −9 m 2 /s) and HAD + EAR (3.218 × 10 −9 m 2 /s). The D eff value of HAD at 60 • C was consistent with previous publications [39,40], ranging from 3.210 × 10 −9 to 2.840 × 10 −8 m 2 /s for the drying of tomato and P. macrocarpa fruits with similar geometries. Furthermore, the D eff value of the RFHAD method were 1.67 times higher compared to that of HAD, which demonstrated that the moisture transfer efficiency of the RFHAD process was much higher than that of HAD.…”
Section: Effective Moisture Diffusivitysupporting
confidence: 90%
“…As the drying temperature increases, the drying rate accelerates, leading to a reduction in the drying time. Similar results have been reported by Stephenus et al for Phaleria macrocarpa (Mahkota Dewa) fruits [18] and by Xie et al for wolfberry [12]. The penetrating heat of FID prevents the surface hardening of the material, consequently enhancing the rate of moisture migration.…”
Section: Moisture Ratiosupporting
confidence: 87%
“…The moisture ratio (MR) of shiitake mushrooms during the thin-layer drying experiments is determined using the following equation [18]:…”
Section: Drying Kineticsmentioning
confidence: 99%
“…Drying temperature has a significant impact on the quality (chemical composition) and can cause physical damage to fruit seeds unless properly optimized. 45,46 In this regard, five different temperatures (313, 323, 333, 343, and 353 K) were selected and used for the drying experiment in a heating furnace. The seed samples were also weighed at specific time intervals to measure the effect of time on the moisture content of the sample.…”
Section: Drying Experiments and Proceduresmentioning
confidence: 99%